Synthesis and fungicidal activity of 1, 3, 4-oxadiazol-2-yl thioether derivatives containing a phenazine-1-carboxylic acid scaffold. Issue 15 (3rd August 2019) - Xingliang, Lu; Xiang, Zhu; Min, Zhang; Qinglai, Wu; Xudong, Zhou; Junkai, Li
Abstract: To find new higher fungicidal activities lead compounds and develop new eco-friendly agrochemicals, natural product phenazine-1-carboxylic acid (PCA) as scaffold, a series of 1, 3, 4-oxadiazol-2-yl thioether derivatives was synthesized and bio-assayed. The results reveal that most target compounds possessed moderate to good fungicidal activities against R. solani, S. sclerotioru and P. oryzac Cavgra. Compounds6n and6o exhibit more than 90% bioactivity against S. sclerotioru . The EC50 value of compounds6n and6o are 11.16 and 30.47 μM respectively, in particular, compound6n show equal activity against S. sclerotioru to PCA (10.49 μM). This result provides a valuable lead compound for further studies. Abstract :